Determinants of the extent to which the operational and running cost affect competitive performance of textile SMEs in Kenya. - Nkondi, Cyprian; Mukulu, Elegwa; Thoruwa, Thomas F.N. (Advances in Social Sciences Research Journal, 2014)
Small and Medium sized entrepreneurial Enterprises (SMEs) play an important role in economic development of many countries in the world. This is because they have potential of employing many people in environments where formal and full wage employment may be scarce or unavailable. SMEs within EPZ are entrepreneurial as they apply creativity and innovation to add value so as meet the needs of their clientele. In Kenya, textile SMEs in Export Processing Zones (EPZ) did well in generating job opportunities to many Kenyans since inception in 2000, contributing 18% of Gross Domestic Product to the national economy. There is limited information on the factors that determine their performance. The purpose of this research was to establish the determinants of the extent to which the operational and running cost affect competitive performance of textile SMEs in Kenya. This research was conducted using descriptive survey. It involved both qualitative and quantitative designs. The design was useful in gaining insights into what goes on among textile SMEs within the Export Processing Zones and therefore provide holistic description of their competitive performance as this will allow the description of the textile SMEs within the Export Processing Zones and hence providing insights of their performance. Given the small number of firms operating these businesses within the Export Processing Zones, an adjusted sample size from small target population was used to select a representative sample of the study using Saunders & Thornhiel formula. This study used interview for owners (IO) and employees in addition to questionnaire for managers (QM) for data collection to achieve the objectives of this study. A pilot test was carried out to test the instruments for corrective purposes, adjustments, validity and reliability. The statistical analyses were facilitated by the use of Statistical Package for Social Sciences (SPSS). The estimate results on average of R2= 72.4% and adjusted average value of R2 = 55.7% indicated that all the independent variables tested were significant determinants of competitive performance of EPZ textile SMEs in Kenya. The study found that credit availability and affordability is essential for their competitive performance, growth and continued profitability. Equally are backward/ local linkages of raw materials, constant sub sector specific policy and regulations and reduced operational costs are critical for their success. The study therefore recommends that quick interventions by the relevant authorities to address the operational and running cost affect to ensure competitive performance of textile SMEs in Kenya.